Implementation of Learning Effect Scheduling on SME’s Injection Moulding Machine - Damur Rochman, Didit; Anwar, Asep; Nugraha, Ucu; Putri, Usi (International Journal of Engineering and Technology, 2018)
This study conducted on SME company in Bandung which have problem on machine scheduling. Current method that company use to schedule job and machine using simple FCFS method which resulting increase inventory and tardiness cost. We proposed machine scheduling with learning effect that developed in the previous research. Using repeat order data, we obtain 20 job that company regularly produce, we calculate scheduling with proposed method and result are 1.71% and 1.81% improvement that FCFS method that company use. Implementation step we proposed to company owner and future work to include quality and time deterioration.Â Â